Evaluasi Strategi Pengendalian Kualitas Permesinan Brake Drum dengan Metoda Attribute Agreement Analysis dan Measurement System Analysis - Pratomo, Edo Suryo; Muhammad Ibrahim; Invanos Tertiana (Jurnal Serambi Engineering, 2026)
In the component manufacturing process in the automotive industry, product quality control strategies affect product defect detection and traceability, production costs, and customer delivery times. To support the achievement of quality assurance in production conditions and production delivery schedules, determining the inspection method of the Pitch Circle Diameter (PCD) on brake drum components becomes important if the operational process capability of the machine is low at Cp = 0.89 and Cpk = 0.83, along with the degradation and age of the machine. The strategy for selecting the use of a Coordinate Measuring Machine (CMM) or a limit gauge for a 100% inspection tool based on the OK/NG classification is evaluated from the aspects of effectiveness, accuracy, and time efficiency. From the evaluation method of the Measurement System Analysis attribute type, specifically Attribute Agreement Analysis, a total of 30 samples were tested by three operators with three replications. The evaluation results showed the effectiveness of the limit gauge of 95.18%, a miss rate of 0%, and a false alarm rate of 7.69%. The Fleiss' Kappa value of the use of the limit gauge was 0.90, indicating good and consistent measurement suitability between operators. Limit gauges showed a measurement time that was 97.7% faster than a CMM (Coordinate Measuring Machine) (17 seconds vs. 740 seconds). The study showed that the strategy of making and using limit gauges as the primary inspection was effective for the need to check 100% of components, under production conditions, with a CMM as a periodic sampling inspection.